Myths of the Martial Arts - Wetzler, Sixt (JOMEC journal, 2014)
This essay tries to identify the recurring patterns of mythic narratives with which martial arts at different times and in different parts of the world have described, explained, and legitimized their modes of action, behaviour, and thinking. It proposes that when examining martial arts as ideological systems, Martial Arts Studies could benefit from incorporating concepts and theories provided by Studies of Religion. The essay is accordingly based on the functionalistic concept of myth as a religious narrative as suggested by Aleida and Jan Assmann in the Handbuch religionswissenschaftlicher Grundbegriffe ('Handbook of basic terms for the Science of Religion'). According to them, three basic functions of myth can be identified: laying foundation, creating legitimation, and forming the world. In the narratives of individual martial arts systems, these three basic functions often utilize one or more standard topoi, some of which are described in the essay: mythical founding figures, zoomorphic movement, geometrical foundation, origin on the battlefield, neo-myths of non-violence. These topoi have been developed and used by individual martial arts without necessary influences between the systems. The aim is not to deconstruct and ridicule such myths, but to point out and understand their importance within the transmission and practice of martial arts.